Uji Efisiensi dan Efektivitas Sistem Notifikasi Pengingat Ujian Seminar pada UIN Alauddin Makassar - Dian Dian; Asrul Azhari Muin; Nahrun Hartono (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This research aims to evaluate the efficiency and effectiveness of seminar exam scheduling at UIN Alauddin Makassar through the development of the DZIKR (Exam Schedule Notification System) application. The problem addressed is the lack of coordination and the potential for miscommunication arising from the manual process of disseminating schedules to lecturers. As a solution, this study developed a web-based exam reminder system integrated with a WhatsApp chatbot to deliver real-time notifications. The methodology involved system development and quantitative analysis to measure its impact. The findings show that the implementation of the DZIKR system significantly improved scheduling efficiency, achieving a rate of 94.5%. However, its effectiveness was recorded at a lower rate of 5.36%. This discrepancy is attributed to the passive nature of the notifications, as the system functions only as a one-way information dispatcher without requiring further user interaction. Nevertheless, it is concluded that the DZIKR system serves as an effective reminder tool that enhances lecturers' awareness of the established schedules. The system has proven successful in addressing the efficiency issue; however, further development is required to incorporate interactive features to boost its overall effectiveness.